PENGARUH LABA DAN ARUS KAS TERHADAP KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fitri Susanti; Rinayanti Rasyad; Jeni Wardi (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2022)
Financial distress is a term that is not commonly heard in public. In fact, financial distress occurs all around us. Losses, inability to pay debts, bankruptcy and default are included in the stage of financial distress. The term that is more familiar to the public is the financial crisis. This study examines whether earnings and cash flow affect the occurence of financial distress conditions by using the Zmijewski method which is still rarely used. Is it true that if profits and cash flows have decreased or are negative, the company is considered to be in financial distress state? Through multiple- regression analysis research methods using Eviews software, and secondary data from www.idx.co.id, the author processed the data to determine the effect of profits and cash flows on the financial distress of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The analysis was carried out by doing assumption test and then proceed with hypothesis testing. The result showing that profits and cash flows have a significant negative effect on financial distress conditions with the probability of profit variable of 0,000 and operating cash flow variable of 0,0114.